ANALYSIS AND FORMATION OF THE ETIOPATHOGENESIS OF DYSBIOSIS IN DENTISTRY (literature review) - Jumaev Eldor, Xaydarkulov Isfandiyor, Narziev Islom, Azamkulov Azimjon (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The formation of normal microbiomaterial of the human oral cavity occurs on the basis of adhesion and the formation of primary colonies of microorganisms to the multilayer flat epithelium of the oral cavity. Scientists identify resistant additional and accidental microflora. A close relationship has been revealed between the formation of resident microflora of the oral cavity during life and such factors as individual features of the structure of the mucous membrane, pathological processes on the oral mucosa, nutrition culture, hygienic aspects, personalized biomechanics of the chewing apparatus, quantitative and qualitative indicators of saliva, saliva secretion, especially in the presence of orthopedic structures. Thus, it was found that even with a violation of the immunophysiological background, the ecosystem of constant normoflora does not participate in the development of dysbiocinosis and has a low pathogenic potential. The causes of changes in the micropease and the occurrence of complications are exogenous factors that disrupt activation by transient and accidental microflora, the ongoing decrease in colonization protection sharply reduces the resistance of the formation of secondary colonization (coadgesis) of opportunistic and pathogenic microorganisms. The additional flora is represented by transient microorganisms coming from the environment, it can be food products, household contact. In a healthy person, representatives of this group are few (up to 105 CFU / 1 ml). With a change in the quantity and quality of the composition of the resident bacterial flora, violation of the functional usefulness of the oral cavity, anatomical integrity, residents of the transient microflora actively form etiopathogenetic links in the occurrence of pathological processes leading to dysbiosis (including candi dose) of the mucosa and allows us to consider these conditions generalized rather than local.